Reliability Analysis Of Distribution System PT. PLN (Persero) ULP Menggala Feeder Pakis With Section Technique Method And Ria-Section Technique Method - rizki, muhammad rizki; Dewi, Arfita Yuana; Erhaneli, Erhaneli; Syofian, Andi; Anugrah, Anggun (JECCOM: International Journal of Electronics Engineering and Applied Science, 2024)
Electricity is a major need today, power companies must ensure the availability of good and sustainable electricity. The continuous and good availability of electric power depends on the reliability of the electric power distribution system. The Section Technique method is a method of assessing system reliability by first dividing the system into several parts and then performing calculations on each part. The RIA-Section Technique method is a combination of RIA techniques and parts that produce results that are close to field data. The reliability indices calculated using this method are SAIFI, SAIDI and CAIDI. The calculation of the 20 kV distribution network reliability index of the Feeder Pakis calculated by the Section Technique method is SAIFI 15.20760 inter / year, SAIDI 17.71123 hours / year and CAIDI is 1.16463 hours / year. For the reliability value of the Feeder Pakis calculated by the RIA-Section Technique method of SAIFI 15.43541 inter / year, SAIDI 17.97542 hours / year and CAIDI of 1.16456 hours / year. The target KPI ULP Menggala in 2023 is SAIFI Value of 6.26 hours/year, SAIDI of 8.43 hours/year and CAIDI of 1.346 hours/year. Meanwhile, the realization of the reliability value of the Feeder Pakis during the period January to December 2023 is SAIFI 3.79 inter / year, SAIDI 3.2 hours / year and CAIDI of 0.845 hours / year